www.I luv perak.com.my (Web based information system) / Noor Aslinamona Muhamad Asral - Muhamad Asral, Noor Aslinamona (2004)
The web site project of WWW.I LUV PERAK.COM.MY (Web Based Information System) is a web based application which makes it more commercial than the current flat web pages. This web site can be viewed by giving information and correct results to the visitors. Basically, the project built upon the problems that arise currently; (1) the delivery of information need is not fully organized in a web site and (2) less eye-catching web site of public point of view. These problems may contribute the lack of participation from publics. Therefore by having this web site project, it will help in providing solution to these problems. This project built using software application such as Macromedia Dreamweaver MX, SWiSHmax, Adobe Photoshop 7.0, and Microsoft Access 2002 (for data storage and retrieval). The Internet Information services (IIS) is acts as the server application which is provided by Microsoft XP Professional. The web programming languages such as HTML, Active Server Pages (ASP) scripts and JavaScript are used to employ dynamic web site project.